The Influence of Total Quality Management (TQM) on the Quality of Health Services at PKM XYZ - Nurul Aziz Pratiwi; Ria Bahriah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted to find out whether there is an influence of Total Quality Management (TQM) on the quality of health services. The research was conducted at one of the PKM located in Kab. Bandung using the Total Quality Management (TQM) method. Data collected in this research was carried out by direct observation and interviews. The results of this research show that TQM has a significant influence on the quality of health services at PKM, namely service quality both partially and simultaneously